2015
DOI: 10.1088/1367-2630/17/4/043046
|View full text |Cite
|
Sign up to set email alerts
|

Interdependent resistor networks with process-based dependency

Abstract: Studies of resilience of interdependent networks have focused on structural dependencies between pairs of nodes across networks but have not included the effects of dynamic processes taking place on the networks. Here we study the effect of dynamic process-based dependencies on a system of interdependent resistor networks. We describe a new class of dependency in which a node's functionality is determined by whether or not it is actually carrying current and not just by its structural connectivity to a spannin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 37 publications
(55 reference statements)
0
12
0
Order By: Relevance
“…However interdependent percolation is limited to systems where functionality is determined exclusively by connectivity: either to the largest connected component [7], backbone [12] or a set of source nodes [13]. It thus provides only a partial understanding of real-world systems, where the network serves as the base upon which a dynamic process occurs [14,15].…”
mentioning
confidence: 99%
“…However interdependent percolation is limited to systems where functionality is determined exclusively by connectivity: either to the largest connected component [7], backbone [12] or a set of source nodes [13]. It thus provides only a partial understanding of real-world systems, where the network serves as the base upon which a dynamic process occurs [14,15].…”
mentioning
confidence: 99%
“…However, this random-like behavior is constrained to the neighborhood of radius z a . Once the damage spreads beyond this neighborhood, it expands linearly in space, with a constant rate and a parabolic decrease in ¥ P , as documented for spatially embedded interdependent networks [31,32,35]. A similar coexistence of random and spatial properties, differentiated by scale, has been observed in the single-layer case [48,63].…”
Section: Resultsmentioning
confidence: 53%
“…Interdependent networks contain layers of networks with two types of links-connectivity links between the nodes in the same layer and dependency links between nodes in different layers. Studies on spatially embedded interdependent networks found that in many cases they are significantly more vulnerable than non-embedded systems [25,[29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…A study on interdependent resistor networks examined the fraction of nodes that carry current, as well as the overall conductivity of the system in the context of process based dependency [99].…”
Section: Realistic Dependency Relationsmentioning
confidence: 99%